PAJAK ATAS PARKIR BERBAYAR BADAN LAYANAN UMUM - Suparna Wijaya; ZAHRONA FATIMAH (Bina Ekonomi, 2020)
The public service agency is a central or regional government agency that provides paid services to the community. Usually, public service agencies also provide paid parking, for example, hospitals. In local government parking tax, parking provision carried out by government agencies is excluded from the tax imposition. Meanwhile, the central government in the Value Added Tax (VAT) provisions excludes parking services. So, the purpose of this study is to explain the comparison of the VAT Law and the Local Taxes Law requirement related to parking provision services, describe the relationship between paid parking from the public service agency and the VAT and the Local Taxes Law provision, and explain the ideal taxation of paid parking provision from the public service agency. The research method used is descriptive qualitative. The results clarify that VAT negative list provision in relation to the Local Taxes Law is one way to avoid double taxation on the same object. Paid parking from public service agency is generally one of the exceptions to the imposition of parking taxes according to the Local Taxes Law because it is a parking space administered by the central government and local governments. However, public service agencies may use third-party services to provide paid parking for its parking lot. This paid parking spaces provision service belongs to a public service agency by a third party is a parking tax based on the Local Taxes Law. Meanwhile, the delivery of parking lot management services carried out by third parties is the object of VAT.